The effect of axially variable thermal and mechanical loads on the 2D thermoelastic response of FG cylindrical shell. Issue 12 (1st December 2016) - Arefi, Mohammad; Faegh, Reza Koohi; Loghman, Abbas
ABSTRACT: This article presents two-dimensional thermoelastic analysis of a functionally graded cylindrical pressure vessel subjected to axially variable thermal and mechanical loads. Thermal and mechanical properties are assumed to be variable along the radius based on the power law variation. Two-dimensional heat transfer equation along the axial and radial directions is analytically solved before thermoelastic analysis of the problem. First-order shear deformation theory is used for description of displacement field. Energy method as well as Euler equation is used to obtain final constitutive differential equations of the system. Four differential equations of the system are solved using the eigenvalue and eigenvector method for various patterns of axially variable loadings. Axial and radial distributions of displacement, strain, and stress components are calculated in terms of different parameters such as variable thermal and mechanical loadings and nonhomogeneous index. The obtained results indicate that the boundary conditions of the cylinder have significant effect on thermoelastic response of the vessel. The axial distribution of displacements, strains, and stresses are validated with the existing literature.